2020
DOI: 10.1002/app.49868
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibrous alginate sulfate scaffolds promote mesenchymal stem cells differentiation to chondrocytes

Abstract: Cartilage tissue engineering is one of the interesting approaches used for repairing cartilage injuries. This study reports the fabrication of polyvinyl alcohol/alginate sulfate (PVA/ALG-S) nanofibrous mats as a functional support for chondrogenic differentiation of human bone marrow mesenchymal stem cells (hBM-MSCs). The PVA/ALG-S nanofibers were obtained through electrospinning of PVA solutions containing 10, 20, and 30 wt% of ALG-S. The appearance of a band at 833 cm −1 assigned to the symmetrical C O S vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The results demonstrated that human bone marrow (hBM) MSCs attach appropriately and spread on the resulting nanofibrous mats. In addition, the results of type-II collagen expression and immunocytochemistry analyses revealed the chondrogenic differentiation of hBM‐MSCs on alginate sulfate nanofibrous mats [ 114 ].…”
Section: Reviewmentioning
confidence: 99%
“…The results demonstrated that human bone marrow (hBM) MSCs attach appropriately and spread on the resulting nanofibrous mats. In addition, the results of type-II collagen expression and immunocytochemistry analyses revealed the chondrogenic differentiation of hBM‐MSCs on alginate sulfate nanofibrous mats [ 114 ].…”
Section: Reviewmentioning
confidence: 99%
“…Alginate sulfate was selected as an efficient substitute for bioactive glycosaminoglycans (GAGs) to be used as a functional support system. The produced nanofibers showed appropriate cytocompatibility and promoted bone marrow mesenchymal stem cells’ growth and differentiation into chondrocytes, demonstrating the great potential of alginate sulfate nanofibers for cartilage tissue engineering applications [ 84 ]. Due to the anti-adhesive properties of alginates, novel anti-adhesion barriers based on alginate electrospun nanofibers have been reported to prevent postoperative peritoneal adhesion [ 85 , 86 ].…”
Section: Seaweed-derived Biopolymersmentioning
confidence: 99%
“…[ 6 ] By exploiting the benefits of emulsion electrospinning, such as providing a simple, affordable, and cost‐effective approach, extensive work has been done to employ this process in the manufacture of core‐shell micro/nanofibrous systems for a wide number of applications, especially sustained or controlled drug delivery. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…SSA has many applications in drug delivery systems and skin tissue engineering because of its biocompatibility, biodegradability, anti‐inflammatory accessibility, and cost‐effective properties. [ 7 ] Due to the negative charge of SSA, it can be useful to entrap the Cu 2+ ion with a positive charge and lead to a sustained release. PVA, as a carrier polymer in the shell part, was expected to reduce the repulsive force between the SSA chains and improve the chain flexibility.…”
Section: Introductionmentioning
confidence: 99%